A Novel Approach for Deriving Nutrient Criteria to Support Good Ecological Status: Application to Coastal and Transitional Waters and Indications for Use - Salas Herrero, Fuensanta; Teixeira, Heliana; Poikane, Sandra (Frontiers in Marine Science, 2019)
A huge variability exists in nutrient concentrations boundaries set for the water (WFD) and the marine strategy framework directives (MSFD), as revealed by a survey to EU member states (MS). Such wide variation poses challenges when checking policy objectives compliance and for setting coherent management goals across European waters. To help MS achieve good ecological status (GES) in surface waters, different statistical approaches have been proposed in a Best Practice Guide (BPG; CIS Nutrients Standards Guidance) for establishing suitable nutrient boundaries. Here we used the intercalibrated results from the WFD for the biological quality element phytoplankton to test the applicability of this BPG for deriving nutrient boundaries in coastal and transitional waters. Overall, the statistical approaches proved adequate for coastal lagoons, but are not always robust to allow deriving nutrient boundaries in other water categories such as estuaries, in transitional waters, or some coastal water types. The datasets available for analysis provided good examples of the most common problems that might be encountered in these water categories. Similar issues have been found in freshwater environments, for which solutions are proposed in the BPG and which are demonstrated here for coastal and transitional waters. The different approaches available and problems identified can be useful for supporting the derivation of nutrient concentrations boundaries both for the Water and the MSFDs implementation.